Forms of Booking on-demand Transport - Hora Jakub; Císařová Hana (Logi, 2025)
This paper examines the interaction between passengers and flexible transport systems, as well as the characteristics of flexible transport systems that are important to users. It presents flexible transport systems introduced in the Czech Republic since 2023 and defines their key parameters. Based on these parameters, evaluation criteria are established and weighted using the Saaty method. The criteria are then categorized according to shared characteristics and weights. The outputs of the Saaty method provide a framework for evaluating and implementing flexible transport systems. To analyse a given area, the authors recommend conducting a SWOT analysis, whose findings can be used for the considered areas of on-demand transport implementation. Subsequently, the findings of the paper can be applied. The paper addresses operations in peripheral areas and during off-peak hours. The aim is to assess the differences between the interaction of individual transport systems with users, and to propose recommendations for optimizing both existing and emerging flexible transport systems.